The emergence of mirror-like response properties from domain-general principles in vision and audition. Issue 2 (29th April 2014) - Saygin, Ayse P.; Dick, Frederic
Abstract Like Cook et al., we suggest that mirror neurons are a fascinating product of cross-modal learning. As predicted by an associative account, responses in motor regions are observed for novel and/or abstract visual stimuli such as point-light and android movements. Domain-specific mirror responses also emerge as a function of audiomotor expertise that is slowly acquired over years of intensive training.